Report on the 17th International Scientific Conference in the “Humanistic Ecology” Series: “Environmental Philosophy and Ethics in the Face of the Ecological Crisis” (Warsaw, 20-21 September 2023) - Sadowski, Ryszad F. (Studia Ecologiae et Bioethicae, 2023)
The report outlines the proceedings of the 17th International Scientific Conference within the “Humanistic Ecology” series (Warsaw, September 2023). The central focus of the event was a philosophical and ethical examination of the escalating ecological crisis, approached from an interdisciplinary standpoint. Emphasis was placed on the necessity of transcending purely technological interventions in favour of humanistic perspectives rooted in anthropological and axiological reflection. The conference brought together scholars of different national and international academic institutions, fostering a dynamic forum for intellectual exchange and collaborative exploration of environmental challenges.